Literature-Integrated Problem-Based Learning for EFL Literary Development: A Qualitative Case Study in a Tertiary Context - Indah Damayanti; Ayu Hudzaifah (Universitas Bengkulu, 2026)
There has been a continuous debate among university lecturers in Indonesia regarding the proper literary theory integrated into literature subjects for undergraduate English education majors. The lecturers argue that literary theory, distinguished by its theoretical density and highly specialized jargon, is immensely daunting for undergraduate students and thus more appropriately taught at the graduate level of literary studies. As a result, the conventional literary classroom system should be shifted into the classroom with an ability to understand, to overcome the problems, and to implement the knowledge into the skills that are useful for contributing to students' success in the current condition. Therefore, implementing PBL in integrating literary theory into teaching English literature is essential in order to address the limitations outlined earlier. A qualitative research approach was employed in this study, utilizing a case study design to investigate a complex phenomenon or event within its natural context. After conducting a case study with the application integrating theoretical frameworks into literary analysis in Literature for Educational Purposes, it has been perceived a more comprehensible understanding of significant academic value has been perceived that literary theories contribute to the undergraduate literature classroom. Students are trained to evaluate, analyze, and give value to the text they have read. The application of literary theories in the literature classroom instruction has been proven to allow students to develop their literary comprehension. Keywords: Case Study, Literary Theory, Literature for Educational Purposes, Problem-Based Learning